DEVELOPMENT OF DISTANCE LEARNING STRATEGIES BASED ON LEARNING MANAGEMENT SYSTEMS TO IMPROVE SELF-DIRECTED LEARNING AND STUDENTS’ UNDERSTANDING OF CONCEPTS - Ahkamsyadid Yusmaputra Salim; Deka Dyah Utami; Agus Wedi (World Psychology, 2026)
Advances in information technology have significantly changed higher education, particularly through the implementation of distance learning. However, challenges remain, including low levels of student self-directed learning and inadequate conceptual understanding. This study aims to develop an LMS-based distance learning strategy in the form of digital learning modules that are valid, practical, and effective in improving student self-directed learning and conceptual understanding. This study uses a research and development (R&D) approach with Dick and Carey's instructional design model. Product validity was evaluated through expert validation, with results of 91% from subject matter experts, 80% from media experts, and 100% from learning design experts, indicating that the product is feasible for implementation. The usefulness and effectiveness were evaluated through small and large group trials and N-Gain analysis. The results of the independent learning questionnaire increased from 83% in the small group trial (practical category) to 97% in the large group trial (very practical category), indicating the high usefulness of the developed product. Additionally, N-Gain analysis showed a significant increase in students' conceptual understanding between pre- and post-tests. These findings indicate that LMS-based distance learning strategies effectively enhance students' self-directed learning and conceptual understanding.